The midnight library ebook - Haig, Matt (2020)
The #1 New York Times bestselling WORLDWIDE phenomenon Winner of the Goodreads Choice Award for Fiction | A Good Morning America Book Club Pick | Independent ( London) Ten Best Books of the Year "A feel-good book guaranteed to lift your spirits." —The Washington Post The dazzling reader-favorite about the choices that go into a life well lived, from the acclaimed author of How To Stop Time and The Comfort Book. Don’t miss Matt Haig’s latest instant New York Times besteller, The Life Impossible , available now Somewhere out beyond the edge of the universe there is a library that contains an infinite number of books, each one the story of another reality. One tells the story of your life as it is, along with another book for the other life you could have lived if you had made a different choice at any point in your life. While we all wonder how our lives might have been, what if you had the chance to go to the library and see for yourself? Would any of these other lives truly be better? In The Midnight Library , Matt Haig's enchanting blockbuster novel, Nora Seed finds herself faced with this decision. Faced with the possibility of changing her life for a new one, following a different career, undoing old breakups, realizing her dreams of becoming a glaciologist; she must search within herself as she travels through the Midnight Library to decide what is truly fulfilling in life, and what makes it worth living in the first place.